Differences in the Effect of Learning Methods and Intelligence Quotient on Handball Learning Outcomes of Students at Public Senior High School 8 Semarang - Kurniawan, Rian; Rahayu, Setya; Hanani, Endang Sri (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
Success in a learning process cannot be separated from the good role and the learning methods used. Educators need to create a pleasant atmosphere so that learning goes as expected. The purpose of this study was to evaluate the differences between inquiry learning methods and directly on student handball learning outcomes at Public Senior High School 8 Semarang, evaluating the differences between high and low levels of intelligence quotient on student handball learning outcomes at Public Senior High School 8 Semarang, and evaluating the interaction between learning methods and intelligence quotient on student handball learning outcomes at Public Senior High School 8 Semarang. This study used an experimental method with a 2x2 factorial design. The subjects in this study were students of class X at Public Senior High School 8 Semarang. This study uses to test and measurement techniques. The instruments used the intelligence quotient test and handball basic ability test. The data analysis technique used two-way Anova statistics, and hypothesis testing with the calculation of the F-test at a significant level of 5%. The results of the study were the distribution of handball learning outcomes of class X students at Public Senior High School 8 Semarang with the inquiry learning method in groups with high intelligence quotient amounting to 73.3% categorized as good, 20% categorized as good enough, and equal to 6.7% categorized as very good. The distribution of handball learning outcomes of class X students at Public Senior High School 8 Semarang with the inquiry learning method in groups with low intelligence quotient is 73.3% categorized as good, and 13.3% categorized as very good and quite good.